(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
There is little doubt that the system of symbols of the modern Russian mass media is completely false and expresses the ideology of consumption, and that this symbolic umbrella is covering the country more and more tightly. Everyone and everywhere, including the media, is saying that something must be done to avoid losing future generations in this ever-increasing system of false symbols. But in order to oppose something, you have to know it. V. Pelevin’s novel Generation ‘P’, the main pathos of which is the rejection of consumer ideology, is of great interest in this sense.